Analgesia Evaluation of 2 NSAID Drugs as Adjuvant in Management of Chronic Temporomandibular Disorders - Fernando Kurita Varoli; Murillo Sucena Pita; Sandra Sato; João Paulo Mardegan Issa; Cássio do Nascimento; Vinícius Pedrazzi (The Scientific World Journal)
The aim of this triple-blind full-randomized clinical trial was to quantify analgesia in masticatory muscles and temporomandibular joints after occlusal splint therapy associated with the adjuvant administration of nonsteroidal anti-inflammatory drugs (NSAID) isolated or associated with other therapeutic agents. Pain relief was also recorded. Eighteen volunteers who had been suffering from chronic pain in masticatory muscles due to temporomandibular disorders were selected after anamnesis and assessment using RDC/TMD translated to Portuguese. The 3 proposed treatments were NSAID (sodium diclofenac), panacea (sodium diclofenac + carisoprodol + acetaminophen + caffeine), and a placebo. The total treatment duration was 10 days, preceded and succeeded by patients’ pain assessment. A washout interval of 11 days was established between each therapy. All participants received all treatments in different moments, in a full randomized crossover methodology. The assessment of drug therapies was performed using visual analogue scale for pain on palpation followed by 11-point numerical scale to quantify pain during treatment. Statistical analysis has shown that, after 10 days of treatment, all therapies were effective for pain relief. NSAID therapy promoted analgesia on the third day, while placebo only promoted analgesia in the eighth day. It has been concluded that sodium diclofenac used as splint adjuvant therapy, promotes significant analgesia in a shorter time.